REPRESENTASI PERJUANGAN SEORANG IBU DALAM FILM NOWHERE ANALISIS SEMIOTIKA CHARLES SANDERS PIERCE - Wahyu Alifian; Edward Enrieco, Panji Suratriadi (STKIP Subang, 2025)
This research aims to analyze the representation of a mother's struggle in the film Nowhere using the semiotic approach of Charles Sanders Peirce. The film portrays a mother's survival journey with her child under life-threatening and challenging conditions. This study employs a descriptive qualitative method with semiotic analysis based on Peirce’s triadic theory of signs: Representamen, Objeks dan Interpretan. The findings reveal that through the use of visual and narrative signs, Nowhere represents the mother as a strong, self-sacrificing, and resilient figure determined to protect her child. Indexes such as body gestures and extreme actions convey deep love and maternal responsibility. Meanwhile, symbols embedded in dialogues and plotlines reinforce the themes of struggle and resilience. The study concludes that Nowhere effectively constructs a heroic narrative of a mother through the use of semiotic structures.